Foreign body in the hypopharynx: late prosthesis extrusion after cervical arthrodesis - Fontes de Oliva Costa, Sofia; Castro, Rafael; Naves, Daniel; Couto, Eduardo (Brazilian Journal of Case Reports, 2023)
This is a case report of a rare airway Foreign Body (FB), the first reported case of an extruded prosthesis of previous cervical spine arthrodesis still attached to the wall of the hypopharynx, obstructing the airway, and requiring immediate removal. A 56-year-old man with a history of previous cervical arthrodesis (C3-C7). He presented anterior displacement of the Cage Device and erosion of the posterior wall of the hypopharynx, with the prosthesis causing partial obstruction of the larynx. After the Neurosurgery and Radiology team determined that there were no risks of cervical spine instability, we were able to remove the device in the operating room using Laryngoscope and McGill forceps with success. After proper evaluation of the case, we were able to remove the foreign body uneventfully. Given the rarity of this complication, we hope this case report can assist in the treatment and management of future cases.